1999
DOI: 10.1093/ajcn/69.1.22
|View full text |Cite
|
Sign up to set email alerts
|

Pentadecanoic acid in serum as a marker for intake of milk fat: relations between intake of milk fat and metabolic risk factors

Abstract: Background:The fatty acid composition of the diet is known to be partially reflected by the fatty acid composition of serum lipids. Objective: We examined whether pentadecanoic acid (15:0) in serum lipids can be used as a marker for intake of milk fat, the major dietary source of 15:0. We also investigated the relations between intake of milk fat and cardiovascular disease risk factors. Design: Sixty-two 70-y-old men completed 7-d dietary records. The intake of milk products was studied in relation to the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
217
2
6

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 280 publications
(252 citation statements)
references
References 36 publications
(39 reference statements)
27
217
2
6
Order By: Relevance
“…Significant correlations, especially for 15 : 0, are reported between intake and levels in adipose tissue and serum (22,23) . 14 : 0 is also abundant in dairy products and some studies confer 14 : 0 in adipose tissue, serum Table 3 Comparison of relative values of fatty acids in erythrocytes (ERY) and fatty acid intakes (g/100 g fat) measured by the FFQ and ten repeated 24 h dietary recalls (24-HDR) in eighty-eight men and ninety-two women from Vä sterbotten County, northern Sweden Erythrocyte membrane fatty acids (% of total fatty acids) Mean intake (g/100 g fat) Spearman correlation coefficient and erythrocytes a role as a biomarker for milk fat (22,24) , but the association may be biased by some endogenous production. Our FFQ measured intakes of 14 : 0, 15 : 0 and 17 : 0 correlated well with 24-HDR-recorded intakes and also correlated positively and statistically significantly (except for 14 : 0 in women) with erythrocyte levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant correlations, especially for 15 : 0, are reported between intake and levels in adipose tissue and serum (22,23) . 14 : 0 is also abundant in dairy products and some studies confer 14 : 0 in adipose tissue, serum Table 3 Comparison of relative values of fatty acids in erythrocytes (ERY) and fatty acid intakes (g/100 g fat) measured by the FFQ and ten repeated 24 h dietary recalls (24-HDR) in eighty-eight men and ninety-two women from Vä sterbotten County, northern Sweden Erythrocyte membrane fatty acids (% of total fatty acids) Mean intake (g/100 g fat) Spearman correlation coefficient and erythrocytes a role as a biomarker for milk fat (22,24) , but the association may be biased by some endogenous production. Our FFQ measured intakes of 14 : 0, 15 : 0 and 17 : 0 correlated well with 24-HDR-recorded intakes and also correlated positively and statistically significantly (except for 14 : 0 in women) with erythrocyte levels.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests 18 : 2n-6 and 18 : 3n-3 as suitable biomarkers, but transformation to longer fatty acids in the same fatty acid series (26) , or possible demand for targeted FFQ design, may weaken the associations. Previous studies on intake and content in biological tissues are also contradictory; only studies using targeted FFQ instruments have displayed significant correlations between intake and tissue contents (1,2,23,27) , while studies failing to find such associations employed FFQ designed to measure overall intakes (24,25,28) . Thus 18 : 2n-6 and 18 : 3n-3 levels in biological tissues, such as adipose tissue, erythrocyte membranes or plasma phospholipids, may reflect intake of these fatty acids, but a very carefully designed recording instrument seems to be a prerequisite to estimate intake sufficiently well.…”
Section: :mentioning
confidence: 99%
“…In the previously reported studies on odd saturated fatty acids in serum, the authors analysed fatty acid pattern in cholesterol esters and phospholipids separately (Wolk et al, 1998(Wolk et al, , 2001Smedman et al, 1999). In spite of analytical differences, the association observed in our present study between the proportion of 15:0 in total serum lipids and adipose tissue, was in the same range as was observed by Smedman et al (1999) and Wolk et al (1998Wolk et al ( , 2001, indicating that 15:0 in serum total lipids may be an equally suitable marker for the intake of dairy fat as the 15:0 content of cholesterol esters and phospholipids. In a previous study, it was observed that very-long-chain n-3 fatty acids in adipose tissue and total serum lipids reflected the dietary intake of very-long-chain n-3 fatty acids to the same degree (Andersen et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that the proportion of 15:0 and 17:0 acid in human adipose tissue (Wolk et al, 1998(Wolk et al, , 2001Baylin et al, 2002) and even in muscle (Andersson et al, 2002) may reflect dairy fat consumption. In addition, two studies have indicated a positive association between the intake of dairy fat and the content of 15:0 in cholesterol esters and phospholipids (Smedman et al, 1999;Wolk et al, 2001). Thus, these odd numbered fatty acids might function as biomarkers for intake of dairy products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation